Suriyeli Mülteci Ergenlerin Yaşadıkları Gelişimsel Sorunların Bazı Demografik Değişkenler Açısından İncelenmesi - Hıdır Apak; Muhammet Cevat Acar (İnsan & Toplum)
This study aims to reveal the developmental problems that Syrian adolescent refugees have experienced under the light of student views that have their education in state schools of the Ministry of National Education. This study is quantitative research in which the survey model was used. The sample of the search comprised of 338 Syrian adolescent refugee students. For data collection tool, socio-demographic data form prepared by the researchers and Developmental Problem Areas Scale (DPAS) was used. The data were analyzed by ANOVA, t-test, LSD, multiple regression analysis test. Exam anxiety, expressing anger, and academic failure were the most significant findings coming near the top that the Syrian adolescent refugees experienced. According the results of the study, the ratio of developmental problems that the adolescents experience was more frequent among girls. Also adolescents who work and have experienced camping life, experience developmental problems more than other adolescents. When the developmental problem areas were analyzed as a whole, it was found that the worse the financial status of the Syrian adolescent refugees is, the more problems they experience.